Anastomosing Hemangioma on 68Ga-DOTATATE PET/CT: A Potential Pitfall. (10th April 2022) - Chua, Wei Ming; Hoe, Kian Ming Jeremy; Dalan, Rinkoo; Too, Chow Wei; Ong, Simon Yew Kuang; Tay, Timothy Kwang Yong; Loke, Kelvin Siu Hoong
Abstract: Anastomosing hemangioma (AH) is a rare benign vascular lesion that primarily involves the genitourinary tract. Cases have also rarely been reported in other organs. AH is often discovered incidentally and resembles angiosarcoma histologically. On imaging, it may mimic other vascular lesions such as renal cell carcinoma and neuroendocrine tumors. We present a case of a 32-year-old woman with incidentally detected AH involving the kidneys, adrenal glands, liver, and retroperitoneum, initially presumed to be neuroendocrine tumors based on imaging findings on CT and 68 Ga-DOTATATE PET scans.